Perception and determinants of Social Networking Sites (SNS) on spreading awareness and panic during the COVID-19 pandemic in Bangladesh - Mohammad Omar Faruk; Popy Devnath; Sanchita Kar; Eshiika Afsana Eshaa; Hakka Naziat (Elsevier, 2022)
Introduction: The COVID-19 pandemic is an unprecedented and unique fallout worldwide and creates colossal disruption in human survival. During the pandemic, social networking sites (SNS) played a significant role in disseminating news related to the pandemic. Methods: This research is based on primary data collected from 400 successful respondents via online Google Form. Bivariate Pearson's Chi-square and multivariate binary logistic regression analysis were performed to determine the impact of the explanatory variables on the study variables. Results: This study reveals that most respondents (n = 360, 90 %) use SNS to get up-to-date news, and 72.5 % (n = 290) read health-related information. The highest number of participants (n = 386, 96.5 %) were Facebook users. Multivariate binary logistic regression reveals that "reading news on SNS" and "sharing information related to COVID-19 on social media" significantly influence the spread of awareness of COVID-19. "Unauthentic news sources" and "stop using social media to stay away from panic" also have a substantial impact on the spread of panic during the COVID-19 pandemic. Conclusion: SNS has become an inevitable medium of information carrier nowadays. Social media users are found significantly aware of the COVID-19 pandemic. The findings of this study might assist the concerned persons in taking the necessary steps to propagate authentic news and regulate appropriate policies to prevent spreading misinformation.